1、把下面的式子代入上面的式子,可以得到x-z=0,因此,x:z=1:1
2、又由下面的式子:x:y=3:1,所以x:y:z=3:1:3
3、令x=z=3,y=1,带进去计算就可以了!
(1)x-3y=0
x=3y y=x/3
4x-3y-3z=0
4x-3*x/3-3z=0
4x-x-3z=0
3x-3z=0
x:z=1:1
(2)因为x:z=1:1 x:y=3:1
所以x:y:z=3:1:3
(3)令x=3y=1z=3
得9
⑴4x-3y-3z=0----①
x=3y------------②
将②代入①,得
4x-x-3z=0-----③
得3x-3z=0
所以x=z x:z=1:1
⑵由②知 x:y=3:1
x:y:z=3:1:3
⑶由⑵知 x=3y z=3y
原式=〔3y*y +2*3y*y〕/〔(3y)^2+y^2-(3y)^2〕=9
解毕
楼主给分~
afxsdgxnwsn
4x-3y-3z=0 -------1
x-3y =0 ------2
(1)由2得 x=3y ----3
将3代入1得 4x-x-3z=0 即x=z
x:z=1:1
(2)x:y:z=3:1:3
(3)因为 x=3y,x=z
3y²+6y²
所以 原式=-----------=9
9y²+y²-9y²